Modeling of the hemodialysis process and integral estimation its efficiency - Бойко, І. Ф.; Поліщук, С. Т.; Шейман, Б. С.; Ключко, О. М.; Білик, С. Д. (Proceedings of National Aviation University (archive), 2021)
On the basis of computer modelling of the hemodialysis process and use of modem mathematical concept about patient as object of control is shown that regimen of artificial kidney equipment which fixed by the personnel of the haemodialysis chronic department is non optimally.